Pemanfaatan Daun Sirih (Piper betle) dalam Tradisi Nginang Masyarakat Adat Lampung sebagai Antibakteri Alami dan Sumber Pembelajaran IPA Berbasis Etnosains - Putri Cahyani; Salya Ristri Pamindya; Sherly Via Zanika; Def Viya Nur Axma; Sabrina Helen Putri; Anisa Aprilia; Qowwi Nurrera; Berti Yolida; Rini Rita T. Marpaung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Piper betle is a plant that has long been utilized by the indigenous Lampung community in the nginang tradition to maintain oral and dental health. This study aimed to describe the use of betel leaves as a natural antibacterial agent in the nginang tradition of the Lampung indigenous community and to examine its potential as an ethnoscience-based science learning resource. This study employed a descriptive qualitative method with an ethnobotanical approach. Data were collected through semi-structured interviews with one traditional leader, five betel leaf users, and three junior high school science teachers selected purposively. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that betel leaves are used to treat various oral health problems, including bad breath, toothache, swollen gums, bleeding gums, and mouth ulcers, either by gargling with boiled betel leaf water or by chewing the leaves directly. This practice is supported by the presence of active compounds that exhibit antibacterial activity against bacteria causing oral health disorders. The evaluation by science teachers indicated that the use of betel leaves in the nginang tradition has strong relevance for integration into ethnoscience-based science learning because it connects local knowledge with scientific concepts in a contextual manner and supports the preservation of the local wisdom of the Lampung community.